Value-added public relations : the secret weapon of integrated marketing - Harris, Thomas L. (Lincolnwood, Ill. : NTC Business Books, 2000)
Business
Keywords: Public relations; Integrated marketing; Marketing communication; Value added customer service; News products; Advertising; Sales promotion